Implementation of Augmented Reality (AR) in Improving Early Childhood Education Teacher Competence: A Case Study in Sawahlunto City - Utoyo, Setiyo; Hazizah, Nur; Syampulma, Hilmainur; Anjelia, Revina; Sri Rahayu R, Ratif (Universitas Negeri Padang, 2025)
This paper presents the outcomes of a community service initiative designed to strengthen the digital competence of Early Childhood Education (ECE) teachers through the implementation of Augmented Reality (AR). Conducted in Sawahlunto City with 15 participating teachers, the program employed a participatory training model consisting of lectures, demonstrations, and hands-on workshops. Teachers were introduced to AR concepts, development tools, and strategies for integrating AR into learning activities in accordance with Developmentally Appropriate Practice (DAP). Quantitative results revealed a 40.3% improvement in teachers’ pretest and posttest scores, indicating enhanced conceptual understanding and technical proficiency. Qualitative observations further showed increased motivation, creativity, and readiness to adopt AR-based media in teaching. The successful development of AR learning products by participants confirms the effectiveness of AR training in advancing technopedagogical competence. These findings underscore the potential of AR as an innovative tool for promoting digital literacy and transforming early childhood learning environments.Keywords: Augmented Reality, ECE teacher competence, digital transformation, digital literacy, learning media.